1996
DOI: 10.1111/j.1439-0450.1996.tb00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Antimicrobial Susceptibility of Obligate Anaerobic Bacteria Recovered from the Uteri of Dairy Cows with Retained Fetal Membranes and Postparturient Endometritis

Abstract: Summary The uteri of 77 postparturient dairy cows were sampled. Samples were cultured aerobically and anaerobically, and the nature of bacterial growth was identified. A mixed aerobic and anaerobic bacterial infection was found in 55 % of the samples. Actinomyces pyogenes was the predominant aerobic species; it was found in 70 % of the samples, whereas Bacteroides melaninogenicus was the most frequent anaerobic species isolated. Altogether, 16 species belonging to the genus Bacteroides were identified with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
1
18
0
2
Order By: Relevance
“…Bonnett et al (1991) found that the co-infection of A. pyogenes with Gram-negative and anaerobic bacteria could increase uterine lesions. In bovine hepatic abscesses, Fusobacterium necrophorum, an anaerobic bacterium, is the primary aetiological agent and co-infects mainly with A. pyogenes, leading to host death (Scanlan & Hathcock, 1983;Roeder et al, 1989;Cohen et al, 1996;Tan et al, 1996). Because forest musk deer are protected by Chinese legislation, experiments on live animals were not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Bonnett et al (1991) found that the co-infection of A. pyogenes with Gram-negative and anaerobic bacteria could increase uterine lesions. In bovine hepatic abscesses, Fusobacterium necrophorum, an anaerobic bacterium, is the primary aetiological agent and co-infects mainly with A. pyogenes, leading to host death (Scanlan & Hathcock, 1983;Roeder et al, 1989;Cohen et al, 1996;Tan et al, 1996). Because forest musk deer are protected by Chinese legislation, experiments on live animals were not possible.…”
Section: Discussionmentioning
confidence: 99%
“…A notable discrepancy was that 5 (17.2%) isolates of A. pyogenes tested in the current study were resistant to penicillin and ampicillin, whereas A. pyogenes from bovine and porcine species, as well as A. pyogenes from non-lung lesions of white-tailed deer with necrobacillosis tested in previous studies, were susceptible to penicillin. 5,6,31 Also, 1 study observed a difference between susceptible patterns of A. pyogenes isolated from bovine udder and bovine uterus to oxytetracycline and trimethoprim-sulfadiazine. 6 Most of the isolates that originated from the uterus were resistant to oxytetracycline and trimethoprim-sulfadiazine, whereas udder isolates were sensitive to both drugs.…”
mentioning
confidence: 99%
“…5,6,31 Also, 1 study observed a difference between susceptible patterns of A. pyogenes isolated from bovine udder and bovine uterus to oxytetracycline and trimethoprim-sulfadiazine. 6 Most of the isolates that originated from the uterus were resistant to oxytetracycline and trimethoprim-sulfadiazine, whereas udder isolates were sensitive to both drugs. 6 Another study found that bovine and porcine isolates of A. pyogenes behaved differently to certain antibacterial drugs where more isolates of porcine origin were resistant to oxytetracycline, erythromycin, tilmicosin, and lincomycin as compared to those isolated from cattle.…”
mentioning
confidence: 99%
See 2 more Smart Citations